Nonverbal communication in early childhood: analysing interactions at Soka Gakkai Singapore kindergarten - youna Chatrine Bachtiar; Devie Rahmawati (Faculty of Communications Science, Dr. Soetomo University, 2025)
The primary objective of this paper is to investigate the participation of young students in interpersonal communication by employing transmission model theory and expectancy violation theory (EVT) as theoretical frameworks. Using qualitative methodology, the author performed direct observations in three classes at Soka Gakkai Singapore (SGS) Kindergarten to record students' communication patterns across vocal, temporal, interactional, and verbal stylistic dimensions. According to the results, the students regularly used moderate speed and loudness of voice in communicating. The kids also showed adaptive speaking techniques mirroring those of native English and Mandarin speakers and engaged in organised dialogues with few interruptions. The students regularly maintained perfect proxemic spacing, which created pleasant surroundings even with uninvited guests. The result is consistent with EVT since it fits societal expectations for pleasant interactions. The coherent, structured communication that was observed demonstrated the transmission paradigm. The findings found that 85% of the observed exchanges followed similar patterns, indicating a dominant communication style. This study provides empirical evidence of effective communication techniques in early childhood settings, giving valuable insights for educators looking to improve young children's communication skills and build supportive learning environments.